2020
DOI: 10.1111/1475-6765.12424
|View full text |Cite
|
Sign up to set email alerts
|

Public support for state surveillance

Abstract: This study examines citizens’ support for state surveillance, contingent upon factors related to policy design and the context of implementation. While most people want to live in a secure environment, we argue in this study that the support of policies to reach this goal depends on their necessity, extensiveness and reliability. Results from survey experiments in four European countries show that citizens are ready to approve the introduction of far‐reaching state surveillance that includes measures of facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
0
19
1
Order By: Relevance
“…This is in line with other experimental studies (such as Helbling et al, 2022), in which a treatment that included terrorist threat did not influence citizens' policy attitudes. However, it contradicts other experimental studies that have successfully shown an impact of terrorist threat on policy support by mentioning the number of victims in the past 3 years in their treatment (Ziller and Helbling, 2021). In the present study, citizens were asked to imagine a terrorist attack.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This is in line with other experimental studies (such as Helbling et al, 2022), in which a treatment that included terrorist threat did not influence citizens' policy attitudes. However, it contradicts other experimental studies that have successfully shown an impact of terrorist threat on policy support by mentioning the number of victims in the past 3 years in their treatment (Ziller and Helbling, 2021). In the present study, citizens were asked to imagine a terrorist attack.…”
Section: Discussioncontrasting
confidence: 60%
“…The term counter-terrorism covers a lot of different policies, ranging from military actions abroad (Gadarian, 2010) to immigration regulations (Helbling and Meierrieks, 2020) and domestic measures such as surveillance (van Leeuwen, 2003;Ziller and Helbling, 2021). In this paper, I operationalize counter-terrorism as a surveillance policy.…”
Section: Threat and Surveillance-the Trade-o Between Security And Civ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study set out to evaluate the role of policy effectiveness in the topical area of state surveillance. Extending the focus of previous studies on counterterrorism or surveillance policy support (see, e.g., Davis & Silver, 2004;Huddy et al, 2005;Ziller & Helbling, 2021), we investigated how the impact of policy effectiveness varies across respondents. We argued that people's perceptions of threat condition how effectiveness considerations relate to policy support.…”
Section: Discussionmentioning
confidence: 99%
“…This means that, by and large, citizens agree on the specific policy goal, whereas the means to reach these goals are more highly contested. Public support for these specific policies may vary and depend upon a range of motives (Ziller & Helbling, 2021). Given the potential for infringements of civil liberties, individuals can be expected to assess the implementation of counterterrorist surveillance measures while taking costs and benefits into account.…”
Section: Policy Effectiveness In the Context Of Counterterrorist Surv...mentioning
confidence: 99%